2008
DOI: 10.1111/j.1469-1795.2007.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of prey responses to wild dogs Lycaon pictus during the denning season on wildlife ranches

Abstract: The spread of game ranching in southern Africa provides opportunities for the reestablishment of populations of endangered wild dogs extirpated by livestock ranchers. However, this potential has not been realized, partly because of negative rancher perceptions. Some ranchers believe that wild dogs impart costs by killing wildlife that could be utilized consumptively. Others complain that wild dogs make ungulates 'skittish' and cause local reductions in prey densities while denning. We compared the skittishness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
7
2
Order By: Relevance
“…This illustrates a behavioural change to avoid lions which, as the dominant carnivore, frequent habitats close to water with greater prey availability (Mills & Biggs, ; Creel & Creel, ). This has been observed before in SVC (Romañach & Lindsey, ), and further examined by Mbizah et al . (), who found that the wild dogs were in fact selecting areas with lower impala densities, rather than consuming or scaring away sufficient prey to cause the reduced density of impalas observed around their dens.…”
Section: Discussionsupporting
confidence: 74%
“…This illustrates a behavioural change to avoid lions which, as the dominant carnivore, frequent habitats close to water with greater prey availability (Mills & Biggs, ; Creel & Creel, ). This has been observed before in SVC (Romañach & Lindsey, ), and further examined by Mbizah et al . (), who found that the wild dogs were in fact selecting areas with lower impala densities, rather than consuming or scaring away sufficient prey to cause the reduced density of impalas observed around their dens.…”
Section: Discussionsupporting
confidence: 74%
“…Although the empirical evidence is weak [ 38 ], anecdotal [ 39 , 40 ] or unsupportive [ 35 , 41 , 42 ], there is evidence that fencing can lead to behavioural changes in some predators. For example, wild dog ( Lycaon pictus ) will incorporate fences into their hunting strategy to significantly increase their ability to take down large prey [ 43 45 ]. These studies raise fundamentally interesting questions that have yet to be fully tested in different ecosystems although the possibility of prey-traps developing at passageways has been raised [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, conservancies are more likely to use livestock management techniques (Schumann, Watson, & Schumann, 2008), require less management of game animals, suffer less impact from predation (Romañach & Lindsey, 2008) and due to economies of scale incur less costs (Lindsey, Romañach, & Davies-Mostert, 2009). Namibia has the largest number of conservancies within the cheetahs' range, with 76 communal conservancies and 20 commercial conservancies (Shaw & Marker, 2011;Shifeta, 2013).…”
Section: Conservanciesmentioning
confidence: 99%